2008
DOI: 10.1158/0008-5472.can-08-0131
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Promotes Mammary Tumor Migration via a Signaling Cascade Involving Protein Kinase C and cdc42

Abstract: Nicotine, one of major components in tobacco, has been shown to be at high concentrations in the blood stream of cigarette smokers. However, the mechanisms of how nicotine affects tumor development and whether nicotine is a potential carcinogen for malignancies induced by second-hand smoking are not fully understood yet. Here, we investigate the signaling pathways by which nicotine potentiates tumorigenesis in human mammary epithelial-like MCF10A or cancerous MCF7 cells. We demonstrate that human MCF10A and MC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 43 publications
(79 reference statements)
6
56
1
Order By: Relevance
“…The findings that nicotine did not induce migration in quiescent A549 cancer cells in the absence of HGF is inconsistent with the results of previous studies, which observed that nicotine itself exerts a pro-migratory effect in various types of cancer cells (10,(12)(13)(14)16,17). The reasoning behind the inconsistent results between the present study and previous studies remains uncertain, however, it may be attributed to differences in the experimental protocol.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings that nicotine did not induce migration in quiescent A549 cancer cells in the absence of HGF is inconsistent with the results of previous studies, which observed that nicotine itself exerts a pro-migratory effect in various types of cancer cells (10,(12)(13)(14)16,17). The reasoning behind the inconsistent results between the present study and previous studies remains uncertain, however, it may be attributed to differences in the experimental protocol.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent evidence suggests that the tumor-promoting effects of nicotine result in increased proliferation, invasion, mesenchymal transition (EMT) and angiogenesis, and decreased cell death and apoptosis (4,(9)(10)(11)(12)(13)(14)(15)(16)(17). However, the molecular mechanisms by which nicotine promotes tumor progression are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…LPA and PA have both been reported to activate PKC signaling, which we have shown to be altered after EDI3 silencing. PKCα has previously been associated with the proliferation, migration, and invasion of tumor cells (36)(37)(38). The observation that EDI3 silencing decreases migration through the PKCα signaling pathway may have important implications for understanding the role of EDI3 in metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…In other cancer cells, nicotine has been shown to affect various signaling cascades that initiated by the binding of its receptor. In breast cancer cells, nicotine was shown to promote cell migration through a signaling cascade involving protein kinase C (PKC) activation and its downstream effector cdc42 (20). In PDA cells, nicotine was shown to induce the expression of prometastasis and pro-angiogenesis osteopontin (OPN) through nAChR and downstream ERK1/2-dependent pathway (21,22).…”
Section: Discussionmentioning
confidence: 99%